Ending Africa's wars progressing to peace - Furley, Oliver; May, Roy (Ashgate, 2006)
Post-colonial Africa has seemingly been in an intractible state of conflict and war for a considerable period of time. This volume explores the process by which these wars were ended, the lessons learnt, and examines the sustainability of recently reconciled conflicts to see how far peace solutions are permanent in this region